Distinct associations of insula and cingulate volume with the cognitive and affective dimensions of alexithymia - Goerlich-Dobre, Katharina Sophia; Bruce, Lori; Martens, Sander; Aleman, André; Hooker, Christine I. (Neuropsychologia, 2014)
Alexithymia (“no words for feelings”) is a major risk factor for psychosomatic and psychiatric conditions characterized by affect dysregulation. The alexithymia personality construct comprises an affective dimension, the level of subjective emotional experience (emotionalizing and fantasizing), and a cognitive dimension, referring to the cognitive control of emotions (identifying, analyzing, and verbalizing feelings). These two dimensions may differentially put individuals at risk for psychopathology, but their specific neural bases have rarely been investigated. Therefore, the aim of the present study was to find out whether the two alexithymia dimensions are associated with discriminable neural correlates. By means of voxel-based morphometry (VBM), differences in gray matter volumes were compared between 20 (10 male) high-scorers and 20 (9 male) low-scorers on the Toronto Alexithymia Scale (TAS-20), reflecting the cognitive alexithymia dimension. In a subset of 32 subjects, the impact of the affective alexithymia dimension was tested in addition, as assessed with the affective subscale of the Bermond–Vorst Alexithymia Questionnaire (BVAQ). Analysis 1 (cognitive alexithymia dimension) revealed significantly larger gray matter volumes in the right posterior insula in high-scorers compared to low-scorers on the TAS-20. Analysis 2 (affective alexithymia dimension) revealed that the affective alexithymia dimension, specifically the emotionalizing factor indicative of low emotional reactivity, was associated with larger gray matter volumes of the right cingulate cortex. These results suggest that the two alexithymia dimensions are associated with distinct structural correlates. •The two alexithymia dimensions are associated with distinct structural correlates.•Right insula volume is larger in high-scorers on the cognitive dimension.•Right cingulate volume is larger in individuals with low emotional reactivity.•Alexithymia should be regarded as a two-dimensional personality construct.